Chipped stone assemblages from Schleswig-Holstein (North Germany) in the collection of the Institute of Archaeological Sciences – ELTE Eötvös Loránd University - Attila Péntek (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae, 2021)
Attila Péntek recently acquired a large amount of chipped stone artefacts from the legacy of his departed friend Peter Nierling († 2017), archaeologist and field researcher in Hamburg. The aim of bequeathing the finds was to support the Palaeolithic and Mesolithic research in Hungary. The beneficiary catalogued the finds according to the sites and together with the necessary documentation handed them over to the Institute of Archeology of the Eötvös Loránd University.